ANALISIS TINGKAT KEPUASAN PELAKU USAHA TERHADAP LAYANAN SERTIFIKASI HALAL SELF-DECLARE OLEH PUSAT HALAL KABUPATEN SUMBAWA - Roos Nana Sucihati; U Usman; E.S. Adi Nusantara (Samalewa: Jurnal Riset & Kajian Manajemen, 2026)
This study aims to determine the level of community satisfaction regarding halal certification services in Sumbawa Regency. This research uses a quantitative descriptive approach. The type of data used in this study is quantitative data obtained directly from primary sources using a questionnaire as an instrument for data collection. The number of respondents in this study was 90 business actors who had been assisted and facilitated to obtain halal certification by the Sumbawa Regency Halal Center during the period November 2024 to October 2025. To obtain an overview of the level of public satisfaction with the performance of halal certification services organized by the Sumbawa Regency Halal Center, nine variables/measurement elements were used referring to the Regulation of the Minister of Administration and Bureaucracy Number 14 of 2017 concerning the measurement of the public satisfaction index towards public services. Based on the results of the research that has been conducted, it was concluded that the implementation of halal certification services at the Sumbawa Regency Halal Center generally shows Good Service Quality (B). The average value of the IKM after conversion was 85.39 and is in the Good (B) category. The service element that received the highest rating from respondents was the competence of service implementers, while the service system, mechanisms and procedures were the service elements that received the lowest ratings from respondents. Thus, the Sumbawa Regency Halal Center has provided good halal certification services for each applicant, although there are several aspects that still require improvement.